Chapel Reflections on the Washington Conference on Evangelicals and Politics in Africa, Asia and Latin America - Samuel, Vinay (Transformation, 2002)
Following the Washington Conference held from June 28-30 2002 on The Bible and the Ballot Box, the final conference of the Study Programme of the International Fellowship of Evangelical Mission Theologians (INFEMIT) on Evangelicals and Politics in Africa, Asia and Latin America, supported by the Pew Charitable Trusts, the project director, Canon Dr Vinay Samuel shared these reflections at a chapel service at the Oxford Centre for Mission Studies. See www.evangelicalsandpolitics.org. Summaries of the regional studies follow this reflection.